2019
DOI: 10.1200/po.18.00323
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Landscape in Resected Periampullary Adenocarcinoma: Relationship With Morphology and Clinical Outcome

Abstract: PURPOSE Periampullary adenocarcinomas encompass a heterogeneous group of tumors with dismal prognosis and limited treatment options. Emerging evidence shows that tumor morphology (ie, intestinal type [I-type] or pancreatobiliary type [PB-type]) is a more relevant prognostic factor than tumor origin. Knowledge is sparse, however, on whether key mutations differ according to morphology. MATERIALS AND METHODS Next-generation sequencing was applied to assess the mutational status of 70 genes in 102 tumors from a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 17 publications
5
16
0
Order By: Relevance
“…NKT cells were more abundant in APC mutated tumors, which may well be explained by the fact that APC mutations were exclusively found in I-type tumors in the current cohort (4). The significantly lower infiltration of CD68 + macrophages in CDKN2A mutated tumors is in line with findings for other types of immune cells (12,22), but may also merely be due to the fact that CDKN2A mutations are more common in PBtype tumors (4). Moreover, in the present study, mDC infiltration was found to be higher in SMAD4 wt tumors, which is in line with a previous study using a different method to assess both immune cell infiltration and mutational status (23).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…NKT cells were more abundant in APC mutated tumors, which may well be explained by the fact that APC mutations were exclusively found in I-type tumors in the current cohort (4). The significantly lower infiltration of CD68 + macrophages in CDKN2A mutated tumors is in line with findings for other types of immune cells (12,22), but may also merely be due to the fact that CDKN2A mutations are more common in PBtype tumors (4). Moreover, in the present study, mDC infiltration was found to be higher in SMAD4 wt tumors, which is in line with a previous study using a different method to assess both immune cell infiltration and mutational status (23).…”
Section: Discussionsupporting
confidence: 92%
“…Next generation DNA sequencing was performed as previously described (4). In brief, the mutational status of 70 commonly cancer-associated genes was assessed using the Illumina TruSeq custom amplicon assay (Illumina, San Diego, United States) according to the instructions obtained from the manufacturer.…”
Section: Targeted Next Generation Dna Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Next‐generation DNA sequencing was performed as previously described . In brief, tissue cores were taken from tumor enriched areas.…”
Section: Methodsmentioning
confidence: 99%
“…Periampullary adenocarcinomas are currently classified by their anatomic location of origin according to the seventh edition of the American Joint Committee on Cancer staging system . They can be divided into two subgroups based on morphology, either intestinal type (I‐type) or pancreatobiliary type (PB‐type), and there is increasing evidence that morphology is a more important determinant of survival than anatomical origin . Survival rates remain dismally low for this group of patients, with 5‐year overall survival (OS) rates of around 6%, partly due to late presentation of the disease, but also because both conventional and targeted therapies have shown limited efficacy.…”
Section: Introductionmentioning
confidence: 99%